Aquatic ecological civilization in cities and green technological innovation for enterprises - Gao, Ruixuan; Wang, Zenan; Zhao, Haifeng (Frontiers in Environmental Science, 2025)
To comprehensively advance the construction of a Beautiful China and achieve harmonious coexistence between humans and nature, the Ministry of Water Resources issued a pilot policy for the development of aquatic ecological civilization cities in 2013, expanding the pilot scope in 2014. This paper investigates whether this policy can promote green technological innovation in enterprises and explores the underlying mechanisms. Utilizing green patent data from listed Chinese enterprises between 2010 and 2018, empirical analysis is conducted through a multi-period difference-in-differences model. The research findings indicate that the construction of aquatic ecological civilization cities significantly enhances green technological innovation among enterprises. Robustness tests confirm the validity of these conclusions. Heterogeneity analysis reveals that that the policy is particularly effective in water pollution intensive industries, state-owned enterprises and eastern regions. Mechanism analysis illustrates that the construction of aquatic ecological civilization cities fosters green technological innovation by reinforcing environmental regulations and alleviating financial constraints on enterprises. The paper recommends a comprehensive implementation of the aquatic ecological civilization city policy, emphasizing enterprise green technological innovation to establish a solid foundation for China’s green economic development.